PENYELESAIAN WANPRESTASI NASABAH DALAM AKAD MUDHARABAH (STUDI KASUS DI BJB SYARIAH KCP PATROL): SETTLEMENT OF CUSTOMER DEFAULTS IN MUDHARABAH CONTRACTS (CASE STUDY AT BJB SYARIAH KCP PATROL) - Milati, Arina; Arifin, Tajul (Al-Muamalat: Jurnal Ekonomi Syariah, 2022)
Defaults can be subject to ta'zir, contract cancellation, risk transfer, or paying for the case. Ta'zir is enforced by Islamic Banks to prevent customers from being negligent about their obligations. The research aims to find out the settlement of default customers, to find out the factors that cause customer defaults, and to find out the results of the analysis regarding DSN Fatwa No. 17/DSN-MUI/IX/2000 regarding procedures for settling defaults in mudharabah contracts at BJB Syariah KCP Patrol. The method used is descriptive qualitative. The results of his research are that settlement of default customers at KCP Patrol is carried out by imposing ta'zir fines and attempts to reprimand via SMS, visiting the customer's house, summoning the customer to come to the bank, giving a subpoena 3 (three) times, to confiscating collateral if the customer is still just don't pay the installments. Factors that cause default customers are a declining business, deliberately delaying payments or being negligent, not having good faith, and sick customers. In conclusion, DSN Fatwa No. 17/DSN-MUI/IX/2000 is not fully implemented because at BJB Syariah KCP Patrol still applies ta'zir fines to all customers without exception. Wanprestasi dapat dikenakan ta'zir, pembatalan kontrak, peralihan risiko, maupun membayar perkaranya. Ta'zir diberlakukan oleh Bank Syariah dalam upaya mencegah nasabah yang lalai akan kewajibannya. Penelitian bertujuan untuk mengetahui penyelesaian nasabah wanprestasi, mengetahui faktor-faktor yang menyebabkan wanprestasi nasabah dan mengetahui hasil analisis mengenai Fatwa DSN No. 17/DSN-MUI/IX/2000 terhadap prosedur penyelesaian wanprestasi dalam akad mudharabah di BJB Syariah KCP Patrol. Metode yang digunakan adalah deskriptif kualitatif. Hasil penelitiannya adalah penyelesaian terhadap nasabah wanprestasi di KCP Patrol dilakukan dengan cara mengenakan denda ta'zir dan upaya teguran melalui SMS, mendatangi rumah nasabah, memanggil nasabah datang ke bank, memberikan surat somasi sebanyak 3 (tiga) kali, hingga penyitaan jaminan apabila nasabah masih saja tidak membayar angsurannya. Faktor-faktor yang menyebabkan nasabah wanprestasi yaitu memiliki usaha yang menurun, sengaja menunda-menunda pembayaran atau lalai, tidak mempunyai itikad baik dan nasabah sakit. Kesimpulannya, Fatwa DSN No. 17/DSN-MUI/IX/2000 tidak sepenuhnya diterapkan karena di BJB Syariah KCP Patrol masih menerapkan denda ta'zir kepada semua nasabah tanpa terkecuali.